Hubungan Antara Rasa Syukur Terhadap Tingkat Depresi, Cemas, Stres Pada Mahasiswa Tingkat Akhir di Masa Peralihan Pandemi Covid-19 - Salim Andeslan; Qurotul Uyun (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The purpose of this study is to investigate the relationship between gratitude and depression, anxiety, and stress in final-year students during the pandemic transition. This study uses quantitative methods with correlation test analysis techniques. The sampling technique used in this study was convenience sampling. The DASS-21 adaptation was used to measure psychological stress, and the gratitude scale was used to measure gratitude. The results of the analysis show that gratitude has a negative and significant correlation with psychological distress (depression, anxiety, and stress) in students. This indicates that the higher the gratitude of the students, the lower their symptoms of depression, stress, and anxiety. The results of this study are expected to serve as a reference for teaching staff to provide socialization, assistance, and reduce the burden of lecturing to respondents, allowing them to maintain the emotional stability of students.